Highly Efficient, Stable, and Ductile Ternary Nonfullerene Organic Solar Cells from a Two‐Donor Polymer Blend. Issue 17 (18th March 2019) - Hu, Huawei; Ye, Long; Ghasemi, Masoud; Balar, Nrup; Rech, Jeromy James; Stuard, Samuel J.; You, Wei; O'Connor, Brendan T.; Ade, Harald
Abstract: Organic solar cells (OSCs) are one of the most promising cost‐effective options for utilizing solar energy, and, while the field of OSCs has progressed rapidly in device performance in the past few years, the stability of nonfullerene OSCs has received less attention. Developing devices with both high performance and long‐term stability remains challenging, particularly if the material choice is restricted by roll‐to‐roll and benign solvent processing requirements and desirable mechanical durability. Building upon the ink (toluene:FTAZ:IT‐M) that broke the 10% benchmark when blade‐coated in air, a second donor material (PBDB‐T) is introduced to stabilize and enhance performance with power conversion efficiency over 13% while keeping toluene as the solvent. More importantly, the ternary OSCs exhibit excellent thermal stability and storage stability while retaining high ductility. The excellent performance and stability are mainly attributed to the inhibition of the crystallization of nonfullerene small‐molecular acceptors (SMAs) by introducing a stiff donor that also shows low miscibility with the nonfullerene SMA and a slightly higher highest occupied molecular orbital (HOMO) than the host polymer. The study indicates that improved stability and performance can be achieved in a synergistic way without significant embrittlement, which will accelerate the future development and application of nonfullerene OSCs. Abstract : A highly efficient, stable, and ductile nonfullerene ternary organic solar cell by integrating two polymer donors and one acceptor is achieved. The enhanced performance and stability are mainly attributed to the suppressed crystallization of the nonfullerene acceptor by introducing a stiff donor that shows low miscibility with the acceptor and a slightly higher highest occupied molecular orbital (HOMO) than the host polymer.